Anesthesia Management for Esophageal Atresia - Feryadi, Rahmat; Riswandi, Riswandi (CoinReads Media Prima, 2025)
Introduction: Esophageal atresia (EA), a congenital anomaly characterized by esophageal discontinuity, often accompanied by tracheoesophageal fistula (TEF), necessitates urgent surgical intervention. This report outlines the anesthesia management for a 9-day-old male infant with EA treated at Zainoel Abidin General Hospital, Banda Aceh. Case Description: The patient presented with clinical symptoms including swallowing difficulty, excessive salivation, and vomiting during feeding, confirmed by nasogastric tube insertion and radiological examination. Initial management involved emergency gastrostomy and esophagostomy for decompression, followed by thoracotomy and esophageal repair using the Foker technique. General anesthesia combined with caudal regional anesthesia was employed to ensure hemodynamic stability and minimize intraoperative opioid requirements. Key anesthetic challenges included the risk of aspiration, difficult airway management, and maintenance of fluid balance and body temperature in a neonate. Postoperatively, the patient was admitted to the neonatal intensive care unit (NICU) with ventilator support, rigorous hemodynamic monitoring, and antibiotic therapy to prevent complications such as infection and respiratory distress. Conclusion: A multidisciplinary anesthetic approach was critical to the successful surgical correction of EA. Early and comprehensive management resulted in a favorable prognosis, highlighting the importance of tailored anesthesia strategies in neonatal surgery.